Analysis of Community Satisfaction with Public Services at the Makassar City Population and Civil Registry Service - Siti Asriana; Muhammad Yusuf Alfian Rendra Anggoro; Arniati (Income Journal Of Economics Development, 2024)
This research aims to determine community satisfaction with the services provided by the Makassar City Dukcapil Office. In this research, the approach used is a qualitative method. The data analysis techniques applied include data reduction, data presentation, and drawing conclusions. The research results show that in general, the services provided to residents are quite good. However, there are several obstacles in the online service process. Not all residents understand how to register online. According to Dukcapil, the millennial generation or younger people are more likely to understand online services. On the other hand, elderly parents often experience difficulties. This is confirmed by researchers' interviews with several elderly residents in Makassar, who stated that they did not understand the online registration process. Meanwhile, younger residents feel that online registration is good and can be done anywhere. To overcome this gap in understanding, Dukcapil has committed to helping elderly residents who come to the location by registering them online. Dukcapil also tries to provide assistance to residents who need help so that all levels of society can benefit from this service. This effort shows that Dukcapil is not only focused on improving service quality, but also trying to ensure service accessibility for all citizens, regardless of age. It is hoped that these steps will increase public satisfaction with Dukcapil services in Makassar City.